Electrical signatures of single-stranded DNA with single base mutations in a nanopore capacitor - Maria E. Gracheva; Aleksei Aksimentiev; Jean-Pierre Leburton (2006)
In this paper, we evaluate the magnitude of the electrical signals produced by DNA translocation through a 1 nm diameter nanopore in a capacitor membrane with a numerical multi-scale approach, and assess the possibility of resolving individual nucleotides as well as their types in the absence of conformational disorder. We show that the maximum recorded voltage caused by the DNA translocation is about 35 mV, while the maximum voltage signal due to the DNA backbone is about 30 mV, and the maximum voltage of a DNA base is about 8 mV. Signals from individual nucleotides can be identified in the recorded voltage traces, suggesting a 1 nm diameter pore in a capacitor can be used to accurately count the number of nucleotides in a DNA strand. Furthermore, we study the effect of a single base substitution on the voltage trace, and calculate the differences among the voltage traces due to a single base mutation for the sequences C3AC7, C3CC7, C3GC7 and C3TC7. The calculated voltage differences are in the 5–10 mV range. The calculated maximum voltage caused by the translocation of individual bases varies from 2 to 9 mV, which is experimentally detectable.